Efektivitas Norm-Referenced Assessment (PAN) dalam Meningkatkan Pemahaman Mata Pelajaran dan Motivasi Siswa: Studi Kasus di SDN 03/III Sungai Deras - Syahril, Muhammad; Remiswal, Remiswal; Khadijah, Khadijah (Lembaga Intelektual Muda (LIM) Maluku, 2024)
This study aims to evaluate the effectiveness of testing based on norms at SDN 03/III Sungai Deras involving 19 grade V students. The research sample was 19 students in grade V at SDN 03/III Sungai Deras. Data were collected through written tests and motivational questionnaires, then analyzed using descriptive statistics and paired t-tests. Results showed a significant increase in the average written test score from 65 to 78 post-intervention, with a corresponding decrease in standard deviation indicating improved consistency. Similarly, the motivation questionnaire revealed an increase in average scores from 3.2 to 4.1 post-intervention, with improved consistency in motivation levels. Statistical analysis confirmed significant differences between pre-test and post-test scores (t = 5.80, p < 0.05). Discussion underscores the positive impact of norm-referenced assessment on enhancing subject understanding and student motivation, emphasizing its relevance in fostering a competitive yet supportive learning.